A Molecular Dynamics Simulation Study: The Inkjet Printing of Graphene Inks on Polyimide Substrates - Lingjun Wu (Frontiers Media S.A., 2021)
Inkjet printing-based 2D materials for flexible electronics have aroused much interest due to their highly low-cost customization and manufacturing resolution. However, there is a lack of investigation and essential understanding of the surface adhesion affected by the printing parameters at the atomic scale. Herein, we conducted a systematic molecular dynamics simulation investigating the inkjet printing of graphitic inks on polyimide substrates under various conditions. Simulations under different temperatures, inkjet velocities, and mechanical loadings such as pressure and deformation are performed. The results show that the best adhesion is achieved in the plasma-modified polyimide/graphene-oxide (mPI/GO) interfacial system (the interaction energy (Ein) between mPI and GO is ca. 1.2 times than with graphene). The adhesion strength decreases with increasing temperature, and higher inkjet velocities lead to both larger impact force as well as interfacial fluctuation, while the latter may result in greater interfacial instability. When loaded with pressure, the adhesion strength reaches a threshold without further improvement as continuing compacting of polymer slabs can hardly be achieved. The detachment of the interfaces was also explored and mPI/GO shows better resistance against delamination. Hopefully, our simulation study paves the way for future inkjet printing-based manufacturing of graphene-based flexible electronics.